Motor and Sensory Features of Cervical Dystonia Subtypes: Data From the Italian Dystonia Registry - Di Biasio, Francesca; Marchese, Roberta; Abbruzzese, Giovanni; Baldi, Ottavia; Esposito, Marcello; Silvestre, Francesco; Tescione, Girolamo; Berardelli, Alfredo; Fabbrini, Giovanni; Ferrazzano, Gina; Pellicciari, Roberta; Eleopra, Roberto; et al. (Frontiers in Neurology, 2020)
Introduction. Cervical dystonia (CD) is one of the most common forms of adult-onset isolated dystonia. Recently, CD has been classified according to the site of onset and spread, in different clinical subgroups, that may represent different clinical entities or pathophysiologic subtypes. In order to support this hypothesis, in this study we have evaluated whether different subgroups of CD, that clinically differ for site of onset and spread, also imply different sensorimotor features. Methods. Clinical and demographic data from 842 patients with CD from the Italian Dystonia Registry were examined. Motor features (head tremor and tremor elsewhere) and sensory features (sensory trick and neck pain) were investigated. We analysed possible associations between motor and sensory features in CD subgroups (focal neck onset, no spread (FNO-NS)); focal neck onset, segmental spread (FNO-SS); focal onset elsewhere with segmental spread to neck (FOE-SS); segmental neck involvement without spread (SNI)). Results. In FNO-NS, FOE-SS and SNI subgroups, head tremor was associated with the presence of tremor elsewhere. Sensory trick was associated with pain in patients with FNO-NS and with head tremor in patients with FNO-SS. Conclusion. The frequent association between head tremor and tremor elsewhere may suggest a common pathophysiological mechanism. Two mechanisms may be hypothesized for sensory trick: a gating mechanism attempting to reduce pain and a sensorimotor mechanism attempting to control tremor.